APPLICATION OF ATTRACTORS FOR IDENTIFICATION DYNAMIC SYSTEMS - Antonov, V. K. (Problems of Informatization and Control, 2021)
An approach to the construction of attractors with given motion properties is proposed for an approximate description of the behavior of nonlinear dynamical systems.